Mechanisms Underlying Overactive Bladder and Interstitial Cystitis/Painful Bladder Syndrome - Grundy, Luke; Caldwell, Ashlee; Brierley, Stuart M. (Frontiers in Neuroscience, 2018)
The bladder is innervated by extrinsic afferents that project into the dorsal horn of the spinal cord, providing sensory input to the micturition centres within the central nervous system. Under normal conditions, the continuous activation of these neurons during bladder distension goes mostly unnoticed. However, for patients with chronic urological disorders such as overactive bladder syndrome (OAB) and interstitial cystitis/painful bladder syndrome (IC/PBS), exaggerated bladder sensation and altered bladder function are common debilitating symptoms. Whilst considered to be separate pathological entities, there is now significant clinical and pre-clinical evidence that both OAB and IC/PBS are related to structural, synaptic, or intrinsic changes in the complex signalling pathways that mediate bladder sensation. This review discusses how urothelial dysfunction, bladder permeability, inflammation, and cross-organ sensitisation between visceral organs can regulate this neuroplasticity. Furthermore, we discuss how the emotional affective component of pain processing, involving dysregulation of the HPA axis and maladaptation to stress, anxiety and depression, can exacerbate aberrant bladder sensation and urological dysfunction. This review reveals the complex nature of urological disorders, highlighting numerous interconnected mechanisms in their pathogenesis. To find appropriate therapeutic treatments for these disorders, it is first essential to understand the mechanisms responsible, incorporating research from every level of the sensory pathway, from bladder to brain.